Crazy Calculus 5

Calculus Level 2

f ( x y ) = f ( x ) f ( y ) \large f\left( \dfrac xy \right) = f( x) - f( y)

Let f ( x ) f(x) be defined for all real x > 1 x > 1 such that it satisfies the above functional equation for all real x x and y y and that f ( e ) = 1 f(e) =1 . Which is of the following options is correct?

  • P : f ( x ) P: f \left( x \right) is bounded
  • Q : f ( 1 x ) 0 Q: f\left( \dfrac 1x \right) \to 0 as x 0 x\to 0
  • R : x f ( x ) 1 R: xf\left( x \right) \to 1 as x 0 x \to 0
  • S : f ( x ) = ln x S: f\left( x \right) =\ln x
P P S S Q Q R R

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tom Engelsman
Sep 2, 2016

If one differentiates the above functional equation with respect to x and y each, then one obtains:

(1/y) f' (x/y) = f' (x) (i), (-x/y^2) f' (x/y) = f' (y) (ii).

Equating (i) with (ii) yields y f' (x) = (-y^2 / x) f' (y) => f' (x) = [-y f' (y)]/x => f' (x) = A/x (iii), where A is an arbitrary real constant. Integrating (iii) will produce f(x) = A ln(x) + B and substituting this expression back into the original functional equation yields:

A ln(x/y) + B = [A ln(x) + B] - [A ln(y) + B] => A ln(x/y) + B = A*ln(x/y)

which forces B = 0. Taking the initial value f(e) = 1 now gives: 1 = A*ln(e) => A = 1, or f(x) = ln(x). Thus, choice S is correct.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...